Pelatihan Pembuatan Minuman Jahe Instan PKK di Desa Tanjung Kecamatan Pajarakan - Novita Lidyana; Dyah Ayu Perwitasari; Mutimmah Rustianawati; Dedi Joko Hermawan; Tedy Herlambang (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) Universitas Panca Marga Probolinggo, 2021)
To maintain body stamina in the Covid-19 conditions that hit the whole world including Indonesia by consuming traditional drinks, such as ginger. Ginger is one of the abundant natural resources in Probolinggo Regency. With a low price and high antioxidant content, this ginger is often found in traditional markets, and some are deliberately cultivated in the yard of the house. In addition, ginger contains a lot of active compounds that are healthy for the body, in the midst of limited supply of vitamin C production and difficult to reach for the lower middle class. Ginger is very helpful in improving the immune system. For this reason, this community service activity which was carried out in Tanjung Village, Pajarakan District, Probolinggo Regency provided training to PKK mothers. This ginger is processed into a traditional drink, in the form of instant ginger in powder form. In this training, it is hoped that PKK women can make instant ginger and package it. So that PKK women in Tanjung Village, Pajarakan District, Probolinggo Regency have the knowledge, skills in making instant ginger drinks properly and correctly, and can package instant ginger drinks that are suitable for sale. Community service activities have been successfully carried out by PKK women in Tanjung Village, Pajarakan District, Probolinggo Regency. Keywords: PKK women, instant ginger, training